2019
DOI: 10.1037/emo0000425
|View full text |Cite
|
Sign up to set email alerts
|

Experimental effects of mindfulness inductions on self-regulation: Systematic review and meta-analysis.

Abstract: Self-regulation is the control of aspects of the self to allow pursuit of long-term goals, and it is proposed as a central pathway through which mindfulness may exert benefits on well-being. However, the effects of a single mindfulness induction on self-regulation are not clear, as there has been no comprehensive review of this evidence. The current review synthesized existing findings relating to the effect of a mindfulness induction delivered in a laboratory setting on measures of self-regulation. Twenty-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 95 publications
(136 reference statements)
7
94
0
3
Order By: Relevance
“…This flexible orienting makes it easier to disengage from salient stimuli/information that is irrelevant for goal-directed behavior. This positive effect of mindfulness on attention orienting was, similarly, reported in a recent meta-analysis of mindfulness induction in laboratory settings ( Leyland et al, 2018 ). It was the FFMQ facets Describing and Non-Judgment that specifically predicted this flexibility of the orienting attention network, which facilitated an efficiency of the flanker incongruent conflict detection.…”
Section: Discussionsupporting
confidence: 81%
“…This flexible orienting makes it easier to disengage from salient stimuli/information that is irrelevant for goal-directed behavior. This positive effect of mindfulness on attention orienting was, similarly, reported in a recent meta-analysis of mindfulness induction in laboratory settings ( Leyland et al, 2018 ). It was the FFMQ facets Describing and Non-Judgment that specifically predicted this flexibility of the orienting attention network, which facilitated an efficiency of the flanker incongruent conflict detection.…”
Section: Discussionsupporting
confidence: 81%
“…Hours of attendance on the other hand was significantly associated with higher improvements in mindfulness, well-being/life satisfaction and reduction of burnout symptoms, supporting the theoretical assumption that mindfulness requires a certain amount of practice (e.g., Bishop et al 2004;Tang et al 2015). Laboratory studies have suggested positive short-term effects of mindfulness inductions (Leyland et al 2018). However, how much minimum training is required to yield sustainable effects remains uncertain.…”
Section: Moderator Analysesmentioning
confidence: 68%
“…Future research may wish to continue utilizing experimental design and behavioral indicators to successfully compliment the current self-report measures of mindfulness to further examine the relationships between constructs (see Arch and Craske 2006;Keng et al 2017;Watford and Stafford 2015). A recent meta-analysis of mindfulness and emotion regulation showcases methodological developments in this research field, and confirms the relationship between these constructs through experimental manipulation (Leyland et al 2018). Within the context of refinement and measurement, the present study aimed to further our understanding of coping and its relationship to the measured constructs by utilizing an alternative scoring of the BriefCOPE (Carver 1997) to produce two contrasting subscales (activity and defeatism; Mohr et al 2014).…”
Section: Limitations and Future Researchmentioning
confidence: 99%